Effectiveness of Cosmos caudatus Extract in Improving Health-Related Parameters among Older Adults with Sarcopenia: A Study Protocol - Nazri, Nurul Syahidah; Vanoh, Divya; Murugaiyah, Vikneswaran; Ibrahim, Baharudin; Kannan, Thirumulu Ponnuraj; Wan Ishak, Wan Rosli; Shahar, Suzana (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This is a randomized, two-arm, double-blind, placebo-controlled study that will be performed among older adults in Kelantan, Malaysia, for 12 weeks. This study aims to determine the effectiveness of a 12-week Cosmos caudatus (C. caudatus) extract supplementation on dietary intake, cognition, mental health, sleep quality, disability, gut microbiota, physical activity, frailty, metabolites, and protein synthesis pathways among older adults with sarcopenia. This study will involve 64 older adults diagnosed with sarcopenia that will be enrolled and randomly allocated with 1:1 ratio, where 32 subjects required in both intervention and placebo group. The intervention group will receive 500 mg/day of C. caudatus supplementation, while the placebo group will be given 500 mg/day of maltodextrin. Study outcomes including sarcopenia status, dementia, motoric cognitive risk, dietary pattern, anthropometric data, physical fitness, mental health, disability and sleep quality will be measured. Blood will be taken for analysis of protein synthesis pathways (using blood plasma) and untargeted metabolomics at baseline and the 12th week. Fecal sample will be collected from a subsample of 24 subjects for gut microbiota analysis. This study is one of the pioneers randomized controlled trials to evaluate C. caudatus efficacy on various health related outcomes among sarcopenic community-dwelling elderly. This study findings are hoped to have the potential to improve health awareness of ulam or fresh salad consumption, specifically C. caudatus and prove its effectiveness as a nutraceutical product for older adults with sarcopenia. The Australian New Zealand Clinical Trials Registry (ANZCTR) has this trial listed as registered with code (ACTRN12623000046606p).